2019
DOI: 10.1097/op9.0000000000000013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breast cancer treatment outcome at Tikur Anbessa Specialized Hospital Adult Oncology Unit, Addis Ababa, Ethiopia

Abstract: Introduction: Breast cancer is a leading cause of death worldwide, and ranks as the fifth cause of death from all cancers, and the most common cause of cancer death in women in both developing and developed countries. However, information regarding treatment outcome of breast cancer is scarce in Ethiopia. Objective: The aim of this study was therefore to assess treatment outcome among breast cancer patients at Tikur Anbessa Specialized Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The study was conducted in the cancer unit of Tikur Anbessa Specialized Hospital, Ethiopia, which is the only tertiary referral hospital in the country with over 700 beds, whereby palliative care services and treatment virtually exist. The hospital has 20 beds devoted to cancer care, and there are three inpatient and two outpatient rooms in the oncology department; on average, 10 adult cancer patients receive palliative care service from the cancer unit of the hospital daily (Dagne et al, 2019).…”
Section: Study Area and Periodmentioning
confidence: 99%
“…The study was conducted in the cancer unit of Tikur Anbessa Specialized Hospital, Ethiopia, which is the only tertiary referral hospital in the country with over 700 beds, whereby palliative care services and treatment virtually exist. The hospital has 20 beds devoted to cancer care, and there are three inpatient and two outpatient rooms in the oncology department; on average, 10 adult cancer patients receive palliative care service from the cancer unit of the hospital daily (Dagne et al, 2019).…”
Section: Study Area and Periodmentioning
confidence: 99%
“…3 Most cancer is usually diagnosed in advanced stages at presentation and most of the patients were young with poor treatment outcomes. 4,5 Having breast cancer is a traumatic experience for both patients and their families and is accompanied by a series of dramatic changes in life including disease-related physical pain or fatigue, and psychosocial problems. In addition, women with breast cancer experience specific emotional problems such as issues of fertility and child bearing; changes in body image related to treatments like losing hair and removed breast.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that the majority of the patients (97.4%) had invasive breast ductal carcinoma, which is in line with other studies conducted in Kenya (84.2%-97.9%) [17][18][19][20] and Ethiopia (95.63%). 12 Besides, a relatively higher number of patients had stage III (42.2%) and stage IV (25%) breast cancer during diagnosis. Furthermore, the study conducted at Aga Khan University Hospital, Kenya, reported that 67.5% of patients were diagnosed at the late stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite those significant benefits, breast cancer treatment outcome is poor. 11 , 12 The condition is worse in developing countries due to the scarcity of healthcare resources and disparity in treatment and healthcare facilities. 13 In addition, patients seek care lately during the advanced stage, which reduces the overall survival.…”
Section: Introductionmentioning
confidence: 99%